A Comprehensive Systematic Review of The Relationship Between Sunscreen Use and Prevention of Photoaging - Betti Merdiani Putri; Metti Herliani Putri (International Medical Journal Corp. Ltd, 2026)
Introduction: Photoaging, the premature aging of skin induced by chronic ultraviolet (UV) radiation exposure, manifests as wrinkles, dyspigmentation, and loss of elasticity. While sunscreen is a cornerstone of photoprotection, the comprehensive evidence linking its use specifically to the prevention of photoaging requires systematic synthesis. This review aims to consolidate the relationship between various photoprotection strategies—including topical sunscreens, oral supplements, antioxidants, and behavioral interventions—and the prevention or amelioration of photoaging. Methods: A systematic review was conducted following predefined screening criteria. Databases were searched for studies involving human participants that investigated sunscreen or photoprotection interventions and reported quantitative outcomes on clinical photoaging measures. Included studies encompassed randomized controlled trials, cohort studies, case-control studies, cross-sectional studies, systematic reviews, and meta-analyses. Data on intervention details, population characteristics, photoaging assessment methods, and outcomes were extracted and analyzed. Results: Sixty-three studies were included. The landmark Nambour trial demonstrated a 24% reduction in skin aging with daily versus discretionary sunscreen use over 4.5 years (Hughes et al., 2013). Shorter-term studies consistently showed significant improvements in wrinkles, pigmentation, and skin texture with regular sunscreen use, with effects evident from 8 to 52 weeks (Randhawa et al., 2016; Sarkar et al., 2019; Du et al., 2020). Enhanced formulations combining UV filters with antioxidants (e.g., vitamin C, bakuchiol), anti-inflammatory agents, or DNA repair enzymes offered superior benefits (Shirata & Maia Campos, 2021; Draelos et al., 2022; Luze et al., 2020). Appearance-based behavioral interventions, such as UV photography and mobile apps, effectively increased sun protection intentions and behaviors, with medium effect sizes (Persson et al., 2018; Brinker et al., 2020). Oral multi-component antioxidant supplements showed promise in increasing minimal erythema dose and improving skin appearance, whereas single-agent β-carotene was ineffective (Stephens et al., 2016; Zhang et al., 2023; Darlington et al., 2003). Discussion: The evidence robustly supports that consistent sunscreen use prevents and can partially reverse signs of photoaging. Efficacy is influenced by formulation, compliance, skin type, and environmental factors. Synergistic effects are observed when UV filtration is combined with agents targeting oxidative stress and inflammation. Behavioral strategies are crucial for fostering long-term adherence. Conclusion: Daily use of broad-spectrum sunscreen, preferably SPF 30 or higher, is a proven, effective strategy for preventing photoaging. Formulations with added antioxidants or anti-inflammatory components provide enhanced protection. Public health initiatives should incorporate appearance-based education to improve sunscreen adherence. Oral antioxidant supplements may serve as adjuncts but not replacements for topical sunscreens.